2019
DOI: 10.1128/aac.01929-18
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Broad-Spectrum Antimicrobial Combination for the Treatment of Staphylococcus aureus and Pseudomonas aeruginosa Corneal Infections

Abstract: Staphylococcus aureus and Pseudomonas aeruginosa are two of the most common causes of bacterial keratitis and corresponding corneal blindness. Accordingly, such infections are predominantly treated with broad-spectrum fluoroquinolones, such as moxifloxacin. Yet, the rising fluoroquinolone resistance has necessitated the development of alternative therapeutic options. Herein, we describe the development of a polymyxin B-trimethoprim (PT) ophthalmic formulation containing the antibiotic rifampin, which exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…Severe PsK cases that require surgical transplantation of donor corneal tissue are often at potential risk of graft tissue rejection (Rush and Rush, 2016). Moreover, constant paucity of transplant tissue and recent emergence of multi-drug resistant (MDR) P. aeruginosa (MDRP) has further added to the challenge to manage PsK (Willcox, 2011; Morita et al, 2014; Vazirani et al, 2015; Tuli and Gray, 2016; Chojnacki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Severe PsK cases that require surgical transplantation of donor corneal tissue are often at potential risk of graft tissue rejection (Rush and Rush, 2016). Moreover, constant paucity of transplant tissue and recent emergence of multi-drug resistant (MDR) P. aeruginosa (MDRP) has further added to the challenge to manage PsK (Willcox, 2011; Morita et al, 2014; Vazirani et al, 2015; Tuli and Gray, 2016; Chojnacki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a pilot study to assess the therapeutic potential of the chemical series RNP0012 was selected for in vivo efficacy in a murine keratitis model of S. aureus infection [ 39 ] because the analog displayed the combination of the most potent anti-staphylococcal activity, low toxicity, and ability to inhibit both RnpA-mediated cellular functions within bacterial cells. Corneal infections were induced by inoculating corneal scratches with S. aureus , eyes were treated with RNP0012 6 h later and every 6 h thereafter for 48 h and bacterial burden was enumerated.…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus is a predominant cause of bacterial keratitis, which is an invasive infection of the cornea and contributes to approximately 2 million worldwide cases of blindness annually [ 17 ]. A corresponding S. aureus keratitis model has been developed in our laboratories that allows an early indication of antibiotic efficacy in the absence of complicating factors such as PK/PD associated with more traditional systemic models of delivery [ 39 ]. In a pilot study using this model we found that scratched murine corneas inoculated with S. aureus show a 1.2 log reduction in bacterial burden in comparison to vehicle treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Effective combinations for S. aureus include meropenem/ciprofloxacin [ 57 ], cefazolin/tobramycin [ 56 ], and polymyxin B-trimethoprim/rifampin [ 58 ]. There are other antibiotics not normally considered for ophthalmology that have been researched in the context of bacterial keratitis; examples include balofloxacin [ 59 ] and tigecycline [ 60 , 61 ]. Both were shown to be potential alternatives to vancomycin.…”
Section: Novel Therapeuticsmentioning
confidence: 99%